Varying processes, similar results: How composition influences fragmentation and subsequent feeding of large pyroclastic density currents - Bernard, Olivier; Bouvet de Maisonneuve, Caroline; Arbaret, Laurent; Nagashima, Kazuhide; Oalmann, Jeffrey; Prabowo, Arief; Ratdomopurbo, Antonius (Frontiers in Earth Science, 2022)
Unlike their silicic counterparts, mafic eruptions are known for being on the low-end of the explosivity spectrum with eruption styles commonly ranging from effusive to Hawaiian fire fountaining. However, there are increasing discoveries of large mafic Plinian eruptions, sometimes generating ignimbrites, suggesting that this phenomenon might not be so uncommon. So, what processes lead a mafic magma to fragment violently enough to generate extensive ignimbrites? We sampled pumices from ignimbrites and PDCs with a compositional range from basaltic-andesite (Curacautín ignimbrite, Volcàn Llaima, Chile), andesite (Marapi, Indonesia) to trachyte (Gunungkawi ignimbrite, Batur, Indonesia). We use SEM imagery and X-ray Microtomography on pyroclasts from these deposits to characterize phenocryst, microlite and vesicle textures. From vesicle number densities we estimate fragmentation decompression rates in the range of 0.4–1.6 MPa/s for the three deposits. With a combination of EPMA and SIMS analyses we characterise pre-eruptive storage conditions. Based on the bulk and groundmass compositions, the storage temperature (1,050–1,100°C), pressure (50–100 MPa) and phenocryst content (1.0–2.5 vol%), we conclude that the basaltic-andesitic Curacautín magma was at sub-liquidus conditions, which allowed fast and widespread disequilibrium matrix crystallization (0–80 vol%) during ascent to the surface. Combined with the important decompression rate, this intense crystallization led to a magma bulk viscosity jump from 103 up to >107 Pa s and allowed it to fragment brittlely. Conversely, for the Marapi PDC and Gunungkawi ignimbrite, similar decompression rates coupled with larger initial bulk viscosities of 105–106 Pa s were sufficient to fragment the magma brittlely. The fragmentation processes for these latter two deposits were slightly different however, with the Marapi PDC fragmentation being mostly driven by vesicle overpressure, while a combination of bubble overpressure and intense strain-rate were the cause of fragmentation for the Gunungkawi ignimbrite. We conclude that mafic ignimbrites can form due to a combination of peculiar storage conditions that lead to strongly non-linear feedback processes in the conduit, particularly intense microlite crystallization on very short timescales coupled with intense decompression rates. Conversely, the high viscosity determined by pre-eruptive storage conditions, including temperature and volatile-content, are key in controlling the formation of more evolved magmas PDCs'.